PENERAPAN MODEL PEMBELAJARAN KOOPERATIF CIRC (COOPERATIVE INTEGRATED READING AND COMPOTION) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Siti Aisyah, Nazwa; Tutun Usman, Asep; Munawaroh, Nenden (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine three aspects: (1) the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model in Islamic Education (PAI), (2) students’ learning outcomes before the implementation of the CIRC learning model, and (3) the improvement of students’ learning outcomes after the implementation of the CIRC learning model. This study employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The research subjects were 19 eighth-grade students at SMP Plus Miftahul Hidayah. Data were collected through observation and learning outcome tests in the form of pretests and posttests. The research instruments were tested for validity and reliability, with 17 items declared valid and a Cronbach’s Alpha value of 0.842, indicating high reliability. The results showed that the implementation of the CIRC learning model was very effective, as indicated by the observation results of teacher and student activities, which obtained a total score of 80 and were categorized as very good. The average pretest score was 65.00, which increased significantly to 93.16 in the posttest. The normality test results showed significance values of 0.561 for the pretest and 0.412 for the posttest (> 0.05), indicating that the data were normally distributed. The homogeneity test showed a significance value of 0.395 (> 0.05), indicating homogeneous data. The paired sample t-test showed a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest results. Furthermore, the N-Gain value was 0.80 or 80%, which falls into the high category. Therefore, it can be concluded that the CIRC learning model is effective in improving students’ learning outcomes in Islamic Education.